Insomnia severity and daytime sleepiness in caregivers of advanced age - Webster, Lucy A.; Ali, Talha; Sharninghausen, Jody; Hajduk, Alexandra M.; Gill, Thomas M.; Miner, Brienne (Frontiers in Sleep, 2024)
Aging-related changes and caregiver burden may increase the risk for sleep disturbances among older caregivers, yet few studies have examined the prevalence of insomnia and daytime sleepiness in this group. We examined the relationship of caregiver status with insomnia and daytime sleepiness among persons of advanced age (>75 years of age). DESIGN: Cross-sectional. SETTING: Community. PARTICIPANTS: Yale Precipitating Events Project participants (n=383, mean age 84.4 years, 67% female, 12% African American, 25% caregivers).Caregivers were persons who reported caring for another person in the past week or caring for/helping a friend or relative >4 times in the past month. We examined the correlates of caregiver status, including demographic (age, sex, race/ethnicity, education, marital status), psychosocial (living alone, Medicaid eligibility, depressive symptoms, social support, hours volunteered), and physical (obesity, chronic conditions, medication use, selfrated health status, physical activity, functional disability, cognitive impairment) factors. We used the Insomnia Severity Index (ISI) to establish insomnia severity (ISI score 0-28) or clinically significant insomnia symptoms (ISI ≥8). We used the Epworth Sleepiness Scale to establish daytime sleepiness (ESS score 0-24) or hypersomnia (ESS ≥10). In nonparametric multivariable regression analyses, we examined the relationship of caregiver status with insomnia or daytime sleepiness.Compared to non-caregivers, caregivers were younger, more educated, less likely to be Medicaid eligible and had lower rates of depression, obesity, poor self-rated health, low physical activity, functional disability, and cognitive impairment . Mean ISI and ESS scores were in the normal range and similar among non-caregivers and caregivers (ISI scores of 6.9+5.6 and 6.9+5.4, and ESS scores of 6.4+4.7 and 6.1+4.3, in non-caregivers and caregivers, respectively). Multivariable-adjusted models demonstrated no significant differences in ISI and ESS scores between non-caregivers and caregivers (regression coefficients for ISI and ESS scores of -0.